2007
DOI: 10.1158/1078-0432.ccr-07-1151
|View full text |Cite
|
Sign up to set email alerts
|

Newer Pathologic Assessment Techniques for Colorectal Carcinoma

Abstract: The pathogenesis of colorectal carcinoma is characterized by progressive genetic abnormalities,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 56 publications
6
35
0
1
Order By: Relevance
“…Several studies have confirmed that an infiltrative tumor border configuration has a significant adverse prognostic impact in colorectal cancer and may predict local recurrence [57,58] . Our study group has also recently provided evidence for the improved stratification of stage Ⅱ colorectal cancer patients based on the diagnosis of tumor border configuration.…”
Section: Tumor Growth Pattern and Prognosismentioning
confidence: 95%
“…Several studies have confirmed that an infiltrative tumor border configuration has a significant adverse prognostic impact in colorectal cancer and may predict local recurrence [57,58] . Our study group has also recently provided evidence for the improved stratification of stage Ⅱ colorectal cancer patients based on the diagnosis of tumor border configuration.…”
Section: Tumor Growth Pattern and Prognosismentioning
confidence: 95%
“…Although the College of American Pathologists has not included budding in its checklist of reportable features, both the Association of Directors of Anatomic and Surgical Pathology and the Union for International Cancer Control recommend its inclusion in routine reporting. 57,58 Our institutional policy is to report the presence or absence of tumor budding in all malignant polyps and colorectal cancer resection specimens. 410 buds in 20 Â field (area not specified)…”
Section: Practical Considerations In the Assessment And Reporting Of mentioning
confidence: 99%
“…Biological markers predictive of poor clinical outcome from the preoperative biopsy would be useful tools to complement clinical staging. To date, such biological markers have had limited impact, including both the molecular analysis of K-ras and p53, as well as immunohistochemical markers (Turner et al, 2007;Guillem et al, 2008). There is currently no tissue-based marker, which is recommended as a prognostic factor by the European Group on Tumour Markers for patients with rectal cancer (Duffy et al, 2007).…”
mentioning
confidence: 99%